Do Metrics Drive News Decisions? Political News Journalists' Exposure and Attitudes Toward Web Analytics. (March 2021) - Lamot, Kenza; Paulussen, Steve; Van Aelst, Peter
As newsrooms are increasingly using web analytics to monitor news behavior, journalism is likely to become increasingly "metrics-driven." Research suggests that analytics are commonly used by web editors to decide on the distribution and promotion of news stories, but how does this affect the news practices of journalists? To what extent are audience metrics taken into account by individual journalists and reporters who work in a specific news beat? This paper explores this question through a survey of political journalists in Belgium. The study examines the level of access that political news journalists have to audience metrics, and to what extent their level of exposure to and use of metrics affects their attitudes toward analytics in news work. Results show that while three quarters of the political news journalists are nowadays exposed to audience metrics on a regular basis, more than half of them report to never make direct use of web metrics in their daily work. Younger journalists are more likely to be exposed and to use web metrics than their senior colleagues, but journalists working for commercial media do not use metrics more intensely than journalists from public service media. Journalists who actively use metrics themselves tend to hold more positive attitudes toward web metrics, whereas the passive exposure to metrics seems to make journalists more skeptical or negative about them.